PENGARUH BAURAN PEMASARAN TERHADAP PEMBELIAN ULANG PRODUK ORIFLAME STUDI PADA JARINGAN YOUNG ENERGETIC SUCCES BUSINESS NETWORK (YESBN) MEMBER ORIFLAME CABANG MEDAN - Karlina, Cici; Harba, Muhammad Dani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2021)
This study aims to determine the effect of the marketing mix on the repurchase of Oriflame products on the Young Energetic Success network The Business Network (YESBN) is a member of the Medan branch of Oriflame. Population in This research is a member of the Young Energetic Success Busines network Network (YESBN), consists of 500 women with a tolerance limit of 10% calculated by Isaac and Michael's calculation formula according to Sugiyono then obtained a sample of 176 respondents with the determination of sample using the Random Sampling technique. The author's data analysis technique used in this research is descriptive quantitative. Data collection in This research was obtained by distributing questionnaires and statistically processed by using the SPSS Version 25 program. From the results of data processing and data analysis with a simple linear regression coefficient that is known as Y =19.226 + 0.441 X, which means, the marketing mix has a significant effect significant to the repurchase variable and from the results of the t-test, count (6.079) > table (1.973); therefore, if the value of count is greater than thetable, then the hypothesis is accepted. So, it can be concluded that the hypothesis that statesvariable (X) has been proven, or in other words, there is a significant effect between thevariable (X) to the variable (Y). Moreover, based on the coefficient test determination of0.419 or with a percentage of 41.9%, the mix marketing effect on repurchase. While othervariables outside this study influenced the remaining 58.1%.